Factors Influencing Generation Z's Intention to Invest in The Capital Market - Muhammad Klana; Muttaqin, Aminnullah Achmad (Contemporary Studies in Economic, Finance and Banking, 2025)
The increase in the number of capital market investors from year to year is dominated by generation Z. The number of generation Z is more than 50% of the total number of capital market investors. This study aims to identify the factors that influence the interest of generation Z in Malang City in investing in the capital market. This research is an exploratory quantitative research with survey method through online questionnaire then using Exploratory Factor Analysis (EFA) for data analysis. The results showed that there are 6 (six) factors that cause students' interest in investing in the capital market, including social media influence factors, investment motivation factors, investment capital factors, investment convenience factors, investment risk factors, and investment return factors. The six factors as a whole have variance that can explain the factors that cause generation Z's interest in Malang City to invest in the Capital Market with a total variance of 67.066%. While the remaining 32.934% is caused by other variables not included in the study.   Abstrak Peningkatan jumlah investor pasar modal dari tahun ke tahun didominasi oleh generasi Z. Jumlah generasi Z lebih dari 50% dari total jumlah investor pasar modal. Penelitian ini bertujuan untuk mengidentifikasi faktor-faktor yang mempengaruhi minat generasi Z di Kota Malang dalam berinvestasi di pasar modal. Penelitian ini merupakan penelitian kuantitatif eksploratori dengan metode survei melalui kuesioner online kemudian menggunakan Eksploratory Factor Analysis (EFA) untuk analisis data. Hasil penelitian menunjukkan bahwa terdapat 6 (enam) faktor yang menyebabkan minat mahasiswa dalam berinvestasi di pasar modal meliputi faktor pengaruh media sosial, faktor motivasi investasi, faktor modal investasi, faktor kemudahan investasi, faktor risiko investasi, dan faktor return investasi. Keenam faktor tersebut secara keseluruhan mempunyai variansi yang dapat menjelaskan faktor-faktor penyebab minat generasi Z di Kota Malang untuk berinvestasi di Pasar Modal dengan total variansi 67,066%. Sedangkan sisanya sebesar 32,934% disebabkan oleh variabel lain yang tidak termasuk dalam penelitian.